Write 9x - 3y = -6 in slope-intercept form. Make sure you show all steps and inverse operations
Answer:
y = 3x + 2 is the slope-intercept form of given equation 9x - 3y = -6
Solution:
Given that we have to write 9x - 3y = -6 in slope intercept form
The slope intercept form is given as:
Where "m" is the slope of the line and "c" is the y - intercept
Let us convert the given equation into slope intercept form
9x - 3y = -6
Keep the variable "y" on one side and move the remaining terms to other side
9x + 6 = 3y
3y = 9x + 6
Move the coefficient of "y" from L.H.S to R.H.S
[tex]y = \frac{1}{3}(9x + 6)[/tex]
Distribute [tex]\frac{1}{3}[/tex] to terms inside bracket
[tex]y = \frac{1}{3} \times 9x + \frac{1}{3} \times 6[/tex]
Simplify the above equation
[tex]y = 3x + 2[/tex]
Thus the slope intercept form is found